Squirrel's family tree - Ferry, Beth (Orchard Books, an imprint of Scholastic Inc., 2019)
"What makes an oak tree an oak tree and what makes a squirrel a squirrel? In Squirrel's Family Tree, things aren't always what they seem. As squirrel searches for, finds, and hides her acorn treasures beneath the shadows of the great oak trees in the forest, little does she know the role she plays in creating the very environment she forages in."--